A Navigating Controversy and Growth: A Sukuk Study in the UK’s Islamic Finance Landscape. - ALLAKI Islam; NAKHCHA Marouane; KHARBOUCH Omar; TLATY Mamdouh (African Scientific Journal, 2024)
Abstract : Sukuk are considered to be hybrid bonds; they can be splited into two main features of stocks and bonds. They are similar to stocks, they precise the type of partnerships and owners of Sukuk for a specific asset or project for finance, in which the Sukuk have been issued. In this paper we will discuss the main different features between the Sukuk and conventional bonds by conducting an appropriate econometric model. Sukuk are new assets in the islamic finance and they are fastly growing in the market, especially with people who follow shari’a law, as they aim to find an asset such as conventional bonds. The paper will use a multiple regression model to see how major macroeconomics variables affect the performance of the Sukuk market and the bonds market. So, we gathered the data for all variables over a period of 10 years between (2008-2018) .As a conclusion, the bonds and Sukuk are affected by different variables, Sukuk are most issued in the real estate field, which is not the case for the bonds. Then, Stock market is positively correlated with Sukuk and negatively correlated for the bonds. Sukuk, often regarded as hybrid bonds, embody a unique blend of stock and bond characteristics, delineating specific partnerships and ownership structures for financing particular assets or projects, aligning with the principles of Islamic finance. This paper aims to elucidate the distinctions between Sukuk and conventional bonds, shedding light on their burgeoning presence within the financial landscape, particularly among adherents of Sharia law seeking Sharia-compliant alternatives akin to conventional bonds. Employing a multiple regression model, we endeavor to analyze the influence of key macroeconomic variables on the performance of both Sukuk and bond markets. Our dataset spans a decade from 2008 to 2018, facilitating a comprehensive examination of market dynamics. In this study, we adopt a post-positivist epistemological perspective, recognizing the partial and conditional nature of knowledge while valuing the importance of observable facts. Utilizing a hypothetico-deductive approach, we formulated hypotheses regarding the relationship between key macroeconomic variables and the performance of sukuk and bond markets. Multiple regression analysis is employed to test these hypotheses and ascertain the significant impact of the variables on market performance. Our analysis reveals distinct differences between sukuk and conventional bonds in terms of issuance patterns and correlations with macroeconomic variables. Sukuk issuance is primarily concentrated in the real estate sector, reflecting its unique position within Islamic finance. Notably, Sukuk issuance predominantly gravitates towards the real estate sector, a departure from conventional bond practices. Additionally, we observe a positive correlation between the stock market and Sukuk performance, in contrast to the negative correlation observed with conventional bonds. keywords: Sukuk, hybrid bonds, Islamic finance, macroeconomic variables, real estate sector, correlation